Prophetic Ethics Education In Response To The Humanitarian Crisis: Actualizing Musa Asy'arie's Prophetic Thought - Erwin, Erwin; Hadi, Rahmad Tri (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
In the midst of the humanitarian and socio-political crises that have plagued the contemporary era, such as moral degradation, ethical disorientation, and inequality, prophetic ethics offers a philosophical path that is founded on transcendental and humanistic values. The purpose of this article is to identify and analyze Musa Asy’arie’s thoughts on prophetic ethics education within the framework of existentialist theocentric anthropocentrism and its relevance in addressing the various crises that have plagued the contemporary era. The research method employed in this study is qualitative research that utilizes a descriptive-analytical approach. The descriptive-analytical approach is considered to be the most appropriate method to explore Musa Asy'arie's thoughts on prophetic ethics education and its actualization in the contemporary socio-political context. The primary data of this study were derived from the works of Musa Asy'arie. Meanwhile, the secondary data of this study were derived from books and other relevant sources that discussed the thoughts and intellectual contributions of Musa Asy'arie. The findings of this study revealed that Musa Asy'arie presents a prophetic ethics paradigm that is founded on divine and humanistic values. In this way, Musa’s theocentric existentialist perspective situates human beings as ethical agents, taking an active part in the establishment of justice, the promotion of spiritual values, and the realization of civilized social transformation. The present research makes a contribution to the enrichment of the Islamic philosophy debate in the present day, with its prophetic ethics model being contextual and relevant to the challenges of the time.